2022
DOI: 10.1021/acscatal.1c05160
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Effect of the Residual Silver on the Electrocatalytic Oxidation of Methanol and Its Intermediates on Nanoporous Gold

Abstract: Nanoporous gold (NPG) obtained by dealloying Ag75Au25 with an overall residual Ag content of less than 1% was investigated as an electrocatalyst for the oxidation of methanol, formaldehyde, and formate in aqueous 0.1 M NaOH solution. The NPG was used to fill cavity microelectrodes, which allowed the recording of well-resolved voltammetry from the porous material. NPG differs from polycrystalline Au (Au­(poly)) by its microstructure and its residual Ag content and also behaves distinctly different than Au­(poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…This proves that there is also a synergistic effect between Ag and Ni/Co atoms on the surface. OH ads plays a very important role in the methanol oxidation process, which can promote the adsorption of methanol, and accelerate the removal of intermediates. , Previous studies have demonstrated that Ag 2 O can efficiently adsorb OH – and form Ag 2 O–OH ads . , We speculate that the reason for the high activity of ANCO-2 is also the adsorption of OH – species by Ag oxides.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…This proves that there is also a synergistic effect between Ag and Ni/Co atoms on the surface. OH ads plays a very important role in the methanol oxidation process, which can promote the adsorption of methanol, and accelerate the removal of intermediates. , Previous studies have demonstrated that Ag 2 O can efficiently adsorb OH – and form Ag 2 O–OH ads . , We speculate that the reason for the high activity of ANCO-2 is also the adsorption of OH – species by Ag oxides.…”
Section: Resultsmentioning
confidence: 87%
“…However, it can be seen from Figure b that the anode peak appears at 1.5 V, and Ag 0 cannot exist at 1.5 V where the oxidation peak appears, so the catalytic performance of ACO on formaldehyde is mainly due to the presence of Co. The high initial current at 1.2 V when the solution contains formaldehyde (Figure b,c) can be attributed to the presence of Ag nanoparticles . The MOR performance of ANCO-2 and its precursor LiNi 0.8 Co 0.2 O 2 is compared and shown in Figure d, and ANCO-2 significantly exhibits a higher oxidation current and much lower onset potential than LiNi 0.8 Co 0.2 O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations